Подання сторонами доказів у судовому розгляді: проблемні питання - Гловюк Ірина Василівна; Гловюк Ирина Васильевна; Glovyuk Iryna V. (My University, 2015)
Стаття присвячена дослідженню визначення моменту подання сторонами доказів у судовому розгляді на основі положень КПК 2012 р. На основі аналізу судової практики сформульовані пропоновані зміни та доповнення до ст.ст. 291, 317, 318, 474 КПК.

Статья посвящена исследованию определения момента подачи сторонами доказательств в судебном разбирательстве на основе положений УПК 2012 г. На основе анализа судебной практики сформулированы предлагаемые изменения и дополнения в ст.ст. 291, 317, 318, 474 УПК.

Criminal procedural code of Ukraine 2012 has forbidden forwarding materials of pre-trial proceedings along with the indictment to a court. Thus issues involved in the right moment of producing evidence by the parties, especially by the prosecution which has the burden of proof in a trial. It has negative consequences in the judicial practice as it’s different on the issue. Lawmaker has made three controversial rules in the Code on the issue of the right moment when parties should forward materials, including the prosecution, to a court of the first instance. Art. 317 of the Code which provides that After the case is assigned for trial, the presiding judge shall be required to provide the opportunity to the participants in court proceedings, if they file a motion thereon, to examine the materials of the criminal proceedings, is in the Section IV «Court Proceedings in the First Instance», but this stage of the criminal process doesn’t provide any cases of establishing of facts and circumstances of the criminal proceeding by examining evidence, except criminal proceeding based on agreements and examining the issue of relief from criminal liability. On the other hand, para. 4 of the Art. 291 of the Code provide that «before commencement of the trial» rise some questions as giving the name of the paragraph 3 of the Chapter 28, the lawmaker interpret the «trial» as the stage of the criminal proceedings in general as well as the part of a trial traditionally called «judicial inquiry» in the law literature so it’s ambiguous to which moment the prohibition is in force. Criminal proceeding based on agreements allows demanding documents, summoning and examining witnesses only to make sure that that the agreement was concluded by the parties thereto voluntarily. According to the articles 291, 317, 318, 474 of the Code should be changed and provisions on the moment of producing evidence by the parties and demanding materials by the court.
Гловюк І. В. Подання сторонами доказів у судовому розгляді: проблемні питання / І. В. Гловюк // Вісник кримінального судочинства. – 2015. - №3. – С. 28-33.
Keywords: підготовче судове провадження; судовий розгляд; матеріали кримінального провадження; обвинувальний акт; угоди; з’ясування обставин кримінального провадження та перевірка їх доказами; подготовительное судебное производство; материалы уголовного производства; обвинительный акт; соглашения; установление обстоятельств уголовного производства и проверка их доказательствами; preparatory proceedings; trial; materials of criminal proceedings; indictment; agreements; ascertaining circumstances and their verification with evidence